Pengaruh Kepemimpinan Transformasional, Kompetensi Kerja dan Motivasi Kerja Terhadap Kinerja Pegawai (ASN) Pada Rumah Sakit Umum Daerah (Rsud) Dabo Kabupaten Lingga - Roni, Roni; Herman, Hendri; Mulyadi, Mulyadi (eScience Humanity Journal, 2024)
This study was conducted with the aim of determining the effect of transformational leadership, work competence and work motivation on employee performance at the Dabo Regional General Hospital (RSUD) of Lingga Regency. The population in this study was 103 employees. The determination of the number of samples used the Slovin formula. So that the number of samples obtained was 82 respondents. The sampling technique was probability sampling. Data collection was carried out by distributing questionnaires to respondents. The collected data was processed using SPSS data processing software. From the results of the study, it is known that partially transformational leadership has no significant effect on employee performance, work competence has a significant effect on employee performance, work motivation has a significant effect on employee performance. Simultaneously, it is known that transformational leadership, work competence and work motivation have a significant effect on employee performance. The adjusted R square value is 0.914 or 91.4%. This means that transformational leadership, work competence and work motivation are able to explain employee performance variables by 91.4%. While the remaining 8.6% is explained by other variables that are not included in this research model.